Prevalence of antibiotic resistance and virulence genes in the biofilms from an aquifer recharged with stormwater. (15th October 2020) - Sidhu, J.P.S.; Gupta, V.V.S.R.; Stange, C.; Ho, J.; Harris, N.; Barry, K.; Gonzalez, D.; Van Nostrand, J.D.; Zhou, J.; Page, D.; Tiehm, A.; Toze, S.
Highlights: Stormwater pathway for entry of pathogenic and opportunistic pathogens into aquifer. Bacteria carrying ARGs and VGs embedded in biofilms survive > 3 months. Multidrug efflux pump (SMR and Mex) and β- lactamase C genes highly prevalent. VGs encoding siderophores, pilin, hemolysin, and type III secretion ubiquitous. Enterobacteriaceae, Pseudomonadaceae, and Bacillaceae major carrier of ARGs and VGs. Abstract: An improved understanding of the diversity and composition of microbial communities carrying antibiotic resistance genes (ARGs) and virulence genes (VGs) in aquifers recharged with stormwater is essential to comprehend potential human health risks from water reuse. A high-throughput functional gene array was used to study the prevalence of ARGs and VGs in aquifer biofilms (n = 27) taken from three boreholes over three months. Bacterial genera annotated as opportunistic pathogens such as Aeromonas, Burkholderia, Pseudomonas, Shewanella, and Vibrio were ubiquitous and abundant in all biofilms. Bacteria from clinically relevant genera, Campylobacter, Enterobacter, Klebsiella, Mycobacterium, Mycoplasma, and Salmonella were detected in biofilms. The mean travel time of stormwater from the injection well to P1 and P3 boreholes was 260 and 360 days respectively. The presence of ARGs and VGs in the biofilms from these boreholes suggest a high spatial movement of ARGs and VGs in the aquifer. The ARGs with the highest abundance were small multidrug resistance efflux pumps (SMR) and multidrug efflux (Mex) followed by β-lactamase C genes. β- lactamase C encoding genes were primarily detected in Enterobacteriaceae, Pseudomonadaceae, Bacillaceae, and Rhodobacteraceae families. The VGs encoding siderophores, including aerobactin ( iro and iuc genes), followed by pilin, hemolysin, and type III secretion were ubiquitous. Canonical correspondence analysis suggested that Total Organic Carbon (TOC), Dissolved Organic Carbon (DOC), turbidity, and Fe concentration has a significant impact on the microbial community structure of bacteria carrying ARGs and VGs. Post abstraction treatment of groundwater may be prudent to improve water security and reduce potential health risks. Graphical abstract: Image, graphical abstract